2005
DOI: 10.1097/01.aids.0000180787.10553.b2
|View full text |Cite
|
Sign up to set email alerts
|

Single (B or C), dual (BC or BD) and triple (BCD) viral hepatitis in HIV-infected patients in Madrid, Spain

Abstract: In our geographic area approximately 5% of HIV infected patients with hepatitis suffer multiple hepatitis virus infection. In patients with triple hepatitis BCD virus infection, HDV appears to be the dominant virus causing inhibition of both HBV and HCV replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 10 publications
3
35
1
Order By: Relevance
“…34 Chronic HDV was recognized in 14% of HIV-positive patients with chronic hepatitis B in EuroSIDA. This rate is lower than in other series which included more IDUs, 35 as more than half (51%) of HBsAg-positive patients in EuroSIDA were MSM, and IDUs only represented a quarter of patients. Delta hepatitis occurred more frequently in HBsAg-positive patients carrying non-A HBV genotypes than in those infected with genotype A (37% versus 6%, respectively), most probably because there was a strong segregation of HBV genotypes by risk group category.…”
Section: Discussioncontrasting
confidence: 59%
“…34 Chronic HDV was recognized in 14% of HIV-positive patients with chronic hepatitis B in EuroSIDA. This rate is lower than in other series which included more IDUs, 35 as more than half (51%) of HBsAg-positive patients in EuroSIDA were MSM, and IDUs only represented a quarter of patients. Delta hepatitis occurred more frequently in HBsAg-positive patients carrying non-A HBV genotypes than in those infected with genotype A (37% versus 6%, respectively), most probably because there was a strong segregation of HBV genotypes by risk group category.…”
Section: Discussioncontrasting
confidence: 59%
“…Injection drug use being the most probable route of HDV transmission for the majority of patients included in our study, HCV infection was also present in many of them. The complex interplay between HBV, HCV and HDV has been described in several previous reports which generally showed HDV to be the dominant virus, often leading to the suppression of HBV as well as HCV 17,22,23 . In line with these findings, only 20% of HIV/HBV/HDV-coinfected patients and 10% of HIV/HBV/HDV-coinfected patients with replicating HDV in our cohort had a replicating HCV infection compared to 60% of HDV-negative individuals.…”
Section: Discussionmentioning
confidence: 86%
“…The role of HDV on HCV replication is not well known, but previous studies have indicated a possible inhibition of HCV by HDV. 21 The absence of HCV re-activation in the sustained responders group is probably indicative of a favorable outcome of a past HCV infection in these patients.…”
Section: Characteristics Of the Patients At Baselinementioning
confidence: 95%